Exogenous calcium reduces boron toxicity by regulating efficient antioxidant system and boron forms in trifoliate rootstock. (3rd July 2022) - Liu, Yalin; Riaz, Muhammad; Lei, Yan; Yu, Zeng; Jiang, Cuncang
Abstract: Boron (B) toxicity is a major limiting factor for crop production, and calcium (Ca) has been reported to alleviate B toxicity. However, mechanisms of Ca alleviating B toxicity in trifoliate rootstock are not clear. Therefore, the present investigation was conducted on trifoliate seedlings to explore the underneath mechanisms. We included two B (10 and 100 µM) and three Ca levels (0, 1.23 and 2.46 mM) to explore the effect of supplementary Ca supply on mitigating B toxicity in order to gain a better understanding of tolerance mechanism in citrus production. The results showed that Ca (2.46 mM) application significantly increased root dry weight and fresh weight by 32.26% and 24.60% under B toxicity condition, respectively. Meanwhile, the root growth was improved with a greater proportion of new roots. The supply of Ca did not reduce the total absorption of B, however, lowered the R-value of B and reduced its utilization efficiency in cell walls. Moreover, Ca also triggered the antioxidant enzyme system to scavenge reactive oxygen species and reduced malondialdehyde content. Nevertheless, total soluble protein did not show any significant effect. Taken together it could be concluded that Ca application can mitigate B toxicity by maintaining antioxidant enzyme system and free B concentration, thereby reducing the utilization efficiency of B in cell wall for avoiding excessive accumulation of B in cells.